Towards Sustainable Preservation: Revitalising Indigenous African Instruments and Craftsmanship - Ntshengedzeni Evans Netshivhambe (E-Journal of Humanities, Arts and Social Sciences)
This study addresses a critical gap in the scholarship of indigenous African music by shifting the focus from preventing the extinction of musical traditions to ensuring the sustainability of indigenous African instruments within academic frameworks. The purpose of the research is to critique the prevalence of the long-prevailing academic approaches employed by Western scholars in African music studies, particularly their failure to emphasise the preservation, modification, and integration of indigenous African instruments in educational settings. These instruments are vital components of sustainable African music education. Using a multi-method approach that includes a review of relevant literature, performance analysis, and interviews with indigenous music practitioners, students, and community members, the study highlighted how previous research on African music studies has predominantly focused on documenting African cultural practices. However, it argued that this documentation does not ensure sustainability if the teaching and performance of these instruments are not integrated into academic and educational practices. The findings revealed that while documenting African music traditions has been a focus for over a century, these efforts are insufficient for sustaining the music if African instruments are not actively incorporated into music-making and pedagogical practices. The study underscores the need for institutions of higher learning and schools to prioritise the inclusion of indigenous African instruments within their curricula. The study contributes to the scholarship on indigenous African music by offering concrete recommendations for education policy and curriculum design. It emphasises the importance of balancing documentation with practical application and suggests that the sustainability of indigenous African music depends on active engagement with its instruments in both academic and performance contexts.